(untitled) - Feng, S. H. (New Jersey, 2003)
Hydrothermal techniques have been widely used in the synthesis of advanced materials, the treatment of wastes, and the preparation and extraction of special chemicals. They have also been studied for the mimicking of geothermal processes. Nowadays, hydrothermal techniques and sciences play a very important role both in industry and in academia. This book includes contributions from chemists and chemical engineering scientists worldwide who are active in the field of hydrothermal reactions and techniques. The topics covered range from fundamentals of hydrothermal reactions, modeling of hydrothermal processes, new techniques for hydrothermal treatment, and new materials from hydrothermal systems to supercritical fluid reaction systems.
Keywords: Hydrothermal processes; Congresses